Implementation of Big Data in the Zoom and Google Classroom Applications as Online Learning Media - Irika Widiasanti; Aisyah Anggie Firsta Zanuara; Dinda Fitri Maulidina; Frima Armedia Rani Atmaja; Sabrina Rida Putri (Indonesian Journal of Education and Mathematical Science, 2023)
Distance or online learning is increasingly becoming a trend in this digital era. Platforms like Zoom and Google Classroom (GCR) are very helpful in supporting online learning. However, how big data on the platform can be utilized as a learning support medium is still an interesting research topic. This article discusses how big data on the Zoom and GCR platforms can be used to improve the quality of online learning. By analyzing user data, personalizing learning, and increasing learning effectiveness, educators can obtain information that is very useful in developing effective learning strategies. However, ethics and user data privacy policies must still be considered in the use of big data on these platforms. In order to improve online learning, the use of big data on the Zoom and GCR platforms can be an effective solution.Keyword : Big Data, Online Learning, User Data Analysis